Evaluation of nano-sized virgin coconut oil (VCO)-loaded liposomes for enhancing mushroom and B16-F10 tyrosinase activity - Suwipa Ungphaiboon; Sutasinee Ardhanwanich; Duangkhae Maneenuan; Sirirat Pinsuwan; Pawika Mahasawat (OpenNano, 2025)
This study evaluated the potential impact of VCO-loaded liposomes, particularly on the activation of tyrosinase. Optimized liposomes containing 1 % (w/w) VCO were prepared using the film deposition on carrier method, resulting in a particle size of 84.02 ± 5.00 nm and a zeta potential of -68.40 ± 2.78 mV. Encapsulation of VCO enhanced mushroom tyrosinase activity by 3-fold and exhibited lower cytotoxicity to B16-F10 cells compared to VCO alone. Moreover, a positive correlation was observed between the increase in intracellular tyrosinase activity and the concentrations of VCO (r = 0.8366) and VCO-loaded liposomes (r = 0.4794) in B16-F10 cells, while a negative correlation (r = -0.0545) was found for liposomes without VCO. A hair and eyebrow-darkening gel containing both VCO and VCO-loaded liposomes further enhanced mushroom tyrosinase activity by 283.33 ± 26.58 %. These findings suggest that VCO-loaded liposomes may serve as novel and effective nano-scale carriers for VCO in cosmetic applications.